"I don't feel any danger because I am in my own community": a photovoice study on adolescents' perceived community safety. Issue 1 (17th December 2021) - Yang, Yingwei; Liller, Karen; Martinez Tyson, Dinorah; Coulter, Martha
Abstract : Purpose: A safe environment is critical for adolescents' well-being. The purpose of this photovoice study is to explore reasons that make adolescents feel safe in their community. Design/methodology/approach: This study was conducted in Florida through both online and in-person recruitment. After a training session on the ethical and technical use of cameras and a brief introduction of the photovoice methodology, six adolescents took photos (n = 66) in their community and discussed their photos guided by the revised SHOWeD framework. Abridged transcripts were used to match photos with corresponding discussions. Thematic analysis was conducted by the research team. Findings: This study identified four main themes related to adolescents' safe perceptions, including community protective factors (n = 22 photos) such as safe physical environments and community cohesion; family protective factors (n = 14 photos) including safe home and caring parents; traffic safety (n = 14 photos), such as proper road signs, seat belts for car safety and helmets and locks for bicycle safety; and public safety (n = 8 photos), such as emergency numbers, fire departments and police cars and officers. Research limitations/implications: Due to the limited number of participants, this study did not compare the similarities and differences of safety perceptions between adolescents living in high crime areas (urban communities) and those in low crime areas (suburban and rural communities). Future photovoice studies are recommended to further explore the influential factors associated with adolescents' perceived community safety in urban and rural areas with different levels of crime rates to provide more evidence on targeted strategies for community safety promotion in each area. Practical implications: By exploring the reasons for adolescents' safe feelings in their community using photovoice, this study provides insights for future intervention programs to promote community safety for children and adolescents from the community, family, traffic and societal perspectives. Social implications: This photovoice study not only empowers adolescents to identify community assets related to their safe perceptions but also illustrates valuable insights for researchers and public health professionals for safety promotion. Originality/value: This study has used a broad research question to explore the reasons that make adolescents feel safe, providing them the opportunities to express their opinions by photo taking and photo discussions. Moreover, rich information at the community, family and societal levels has been collected as related to factors contributing to adolescents' safe perceptions, adding to the literature on community safety. In addition, this photovoice study has offered both in-person and online participation. Such combination not only provides adolescents with an opportunity to choose a participation method that works best for them but also adds to the photovoice methodology by extending the data collection from in-person to online.